If $\{s_n\}$ is a complex sequence, define its arithmetic mean $\sigma_n$, by


Put $a_n=s_n-s_{n-1}$ for $n\ge 1$. Assume $M<\infty$, $|na_n|\le M$ for all $n$, and $\lim\sigma_n=\sigma$. Prove that $\lim s_n=\sigma$, by completing to following outline:

If $m<n$, then $$s_n-\sigma_n={m+1\over n-m}(\sigma_n-\sigma_m)+\frac1{n-m}\sum_{i=m+1}^n(s_n-s_i).\tag{1}\label{1}$$

For the $k$ in the last term, show

$$|s_n-s_k|\le{n-m-1\over m+2}M.\tag{2}\label{2}$$

Fix $\epsilon>0$ and associate with each $n$ the integer $m$ that satisfies

$$m\le{n-\epsilon\over 1+\epsilon}<m+1.$$

Then $$(m+1)/(n-m)\le\frac1\epsilon \text{ and } |s_n-s_k|\le M\epsilon.\tag{3}\label{3}$$ Hence $$\limsup_{n\to\infty}|s_n-\sigma|\le M\epsilon.\tag{4}\label{4}$$

I've worked through $\eqref{1}-\eqref{3}$, but having trouble with $\eqref{4}$.

My attempt:

Choose $m$ and $n$ so that $|\sigma-\sigma_m|<\epsilon$, then

$$\begin{align} \limsup_{n\to\infty}|s_n-\sigma| & \le\limsup_{n\to\infty}|s_n-\sigma_n|+\limsup_{n\to\infty}|\sigma_n-\sigma|\\ & =\limsup_{n\to\infty}|s_n-\sigma_n|\\ & \le{m+1\over n-m}\limsup_{n\to\infty}|(\sigma_n-\sigma_m)|\\ &\quad\quad+\frac1{n-m}\limsup_{n\to\infty}\sum_{k=m+1}^n|s_n-s_k|\\ & \le\frac1\epsilon|\sigma-\sigma_m|+M\epsilon\\ &\color{red}{\le 1+M\epsilon}. \end{align}$$

I don't know how to do this without getting the $1$ term.


I agree with most of your work. A couple of notes:

  • "Choose $m$ and $n$ so that $|\sigma-\sigma_m|<\epsilon$" doesn't really make sense since $m$ is predetermined by your choice of $n$ and $\epsilon$.
  • All of the instances of $n$ and $m$ should still be contained within the $\limsup$'s.

So with these small alterations you can still get $$\limsup_{n\to\infty}|s_n-\sigma|\leq\frac{1}{\epsilon}\limsup_{n\to\infty}|\sigma_n-\sigma_m|+M\epsilon.$$

But since $\{\sigma_n\}$ is convergent and $\frac{n-\epsilon}{1+\epsilon}<m+1$ implies $m\to\infty$ as $n\to\infty$, we have


and the desired result follows.

  • $\begingroup$ I see your point about all instances of $m$ and $n$ being inside $\limsup$. If I'm understanding correcg $\endgroup$ – Tim Raczkowski Jan 17 '15 at 8:44
  • $\begingroup$ Correctly, the point of the bound $(m+1)/(n-m)<1/\epsilon$ is to replace $(m+1)/(n-m)$ with a constant so that the first term can vanish as $n,m\to\infty$. The fact that $1/\epsilon$ gets large as $\epsilon$ gets small is irrelevant as long as we let $n,m\to\infty$ first. $\endgroup$ – Tim Raczkowski Jan 17 '15 at 9:01
  • $\begingroup$ Right, since $\epsilon$ is fixed in advance, we've shown that the term goes to zero no matter how small $\epsilon$ is. $\endgroup$ – AMPerrine Jan 17 '15 at 15:01

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.